Travel intention during the COVID-19 epidemic: The influence of institutional and interpersonal trust - Li, Wenyong; Chen, Gang; Wu, Lunwen; Zeng, Yanling; Wei, Jing; Liu, Yao (Frontiers in Psychology, 2022)
The global pandemic, COVID-19, has dealt a heavy blow to the tourism industry. Therefore, exploring the mechanisms influencing travel intention in the post-epidemic era can help provide management insights for the recovery of the travel market. Relying on the logic of social cognition theory, we conducted an empirical analysis from the perspective of trust and found that institutional trust and interpersonal trust can positively predict travel intention in the context of the epidemic, while travelers’ health risk perception and safety self-efficacy mediate the relationship between trust and travel intention. Moreover, we verified the moderating role of tourists’ psychological resilience. Further, the study confirms that China’s active prevention policy not only reduces the physical health harm caused by the epidemic, but also effectively increases individuals’ institutional trust in a proactive government. Through China’s active anti-epidemic policy, individuals were able to counteract the negative impact of the COVID 19 epidemic on their travel intention. Further, theoretical and practical implications are discussed.